Paraclinical Study Of The Saliva Ph Modifications For The Complete Edentulous Patients - Rodica Murineanu; Corina Laura Stefanescu; Agripina Zaharia; Carolina Davidescu (Romanian Society of Oral Rehabilitation, 2009)
In practice we have encountered many situations in which all complete edentulous patients, whom we treated with complete dentures had to keep the disturbance caused by the changes occurring prosthetic components in the salivary fluid. Assessment of changes that occur in all complete edentulous patients wears or not, in terms of salivary pH. Material and method: The study was conducted over a period of two years in Clinic Dental Prosthetics, Social Center of the Faculty of Dentistry and the Old people's homes in Constanta. Lot studied was composed of a total of 80 patients in which 40 patients with different types of edentation and 40 complete edentulous patients. As methods we used to determine salivary pH by digital pH meter and salivary strips. Results and conclusions: Changes in salivary pH depends on age, gender, edentation specific features, but considering the impossibility of achieving correlations between indicators in the control group, we can conclude that there are wide individual variations that depend on other factors such as, nutrition, fluid intake, medication daily or occasional, and not least the types of existing prosthetic treatment can induce changes in the quality and quantity of saliva. It may indicate that salivary strips method is less accurate and less subjective, values are determined by a fairly large degree of error. Overall average pH value in batch toothless decreases with age and edentation maturity and is much more increased in female patients. Comparing the two groups, the average pH value decreases from patients with different degrees of edentation at complete edentulous group regardless of age group or gender.